New horizons and global perspectives in female entrepreneurship research - Cullen, Ufuk Alpsahin (Emerald Publishing Limited, 2023)
The study of female entrepreneurship in business is well established in the context of western nations, but it is severely lacking beyond this context. This situation hinders the growth of female enterprises into emerging markets and discourages opportunities for business collaboration. New Horizons and Global Perspectives in Female Entrepreneurship Research offers a collection of high-level case studies by academics and researchers from underdeveloped and developing countries in order to provide better insights into the global markets for the Western (female) entrepreneur. Providing much needed research and inquiry, the authors introduce various aspects of the female entrepreneur - such as her entrepreneurial process, interaction between the female entrepreneur and the institutional context surrounding her - introducing new avenues of exploration and collaboration. Enhancing and encouraging female entrepreneurship research and participation, New Horizons and Global Perspectives in Female Entrepreneurship Research is innovative contribution to business and enterprise.